Impacts of hunting prohibitions on multidimensional well-being. (March 2020) - Strong, Michael; Silva, Julie A.
Abstract: Prohibitions against wildlife hunting often have impoverishing outcomes for rural households. Previous research has emphasized the financial losses and attributed material deprivation as the motivation for illegal wildlife hunting. However, this narrow focus does not capture the values rural communities ascribe to hunting nor consider the broader outcomes hunting bans have on multidimensional well-being. In this study, we utilize Amartya Sen's capability approach to gain a deeper understanding of hunting bans' effects. Iterative content analysis of 435 interviews with respondents from three study sites located within or near protected areas in southern Africa revealed that individuals hunt for three primary reasons: to procure meat for household consumption, to manage human-wildlife conflict, and to generate revenue via commercial poaching. When detailing the impacts of hunting prohibitions, respondents overwhelmingly emphasized the instrumental value of hunting. They described significant material losses that are deeply intertwined with a broad range of non-material costs to well-being. The strongest objections to wildlife regulations centered on how they serve to humanize animals while de-humanizing people. Additionally, the non-material impacts of hunting bans exacerbated discontent with material losses arising from conservation. We find a need to critically examine the non-material losses of conservation given their potential to alienate rural communities, increase resistance, and undermine local residents' voluntary participation in conservation efforts. Highlights: Anti-hunting laws can undermine the legitimacy of conservation initiatives. Hunting was valued for primarily material reasons. Enforcement of anti-hunting laws diminishes multiple dimensions of well-being. Non-material costs of hunting bans exacerbate discontent with the material losses. Resistance motives for illegal wildlife hunting can emerge and strengthen over time.